2021
DOI: 10.1002/essoar.10506436.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

"Shaking in 5 seconds!" A Voluntary Smartphone-based Earthquake Early Warning System

Abstract: Public earthquake early warning systems have the potential to reduce individual risk by warning people of an incoming tremor, but their development is hampered by costly infrastructure. Furthermore, users' understanding of such a service and their reactions to warnings remains poorly studied. The Earthquake Network app turns users' smartphones into motion detectors and provides rapid information about felt earthquakes in multiple countries. It offers an alternative without the need of dedicated infrastructure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…By analyzing the results of a questionnaire (n = 2625) sent to EQN users following a warning issued for an M 8.0 earthquake that hit Peru in 2019, we assess how the system's characteristics affected users' perceptions and responses to the warning. This piece of research complements a previous article (Bossu et al, 2021) that focused on EQN's technical performance and showed that despite a good understanding of the warning, only 25% of respondents took protective action.…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…By analyzing the results of a questionnaire (n = 2625) sent to EQN users following a warning issued for an M 8.0 earthquake that hit Peru in 2019, we assess how the system's characteristics affected users' perceptions and responses to the warning. This piece of research complements a previous article (Bossu et al, 2021) that focused on EQN's technical performance and showed that despite a good understanding of the warning, only 25% of respondents took protective action.…”
Section: Introductionsupporting
confidence: 70%
“…1). If not too close to the detection point, users may then receive a warning in advance of the seismic wave that causes the shaking and thus benefit from an earthquake early warning (EEW) (Finazzi, 2016;Bossu et al, 2021). The EQN app is free to download, available in eight languages, and can be run all over the globe.…”
Section: Elements Of Context: Eqn Warnings and The M 80 Earthquake In...mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the decentralised EEW sensor network architecture proposed in this paper shows that the detection of earthquakes and processing of ground-motion data can successfully be implemented at the sensor node. This research explored and implemented an experimental EEW system by employing 100% decentralised processing compared to the currently available EEW approaches based on centralised processing [8,11,41,87]. Even though Fischer and colleagues proposed a decentralised EEW approach, there are no clear findings of the robustness of their system [15].…”
Section: Discussionmentioning
confidence: 99%